Daytime Sleepiness Is Associated With Reduced Integration of Temporally Distant Outcomes on the Iowa Gambling Task. Issue 2 (3rd March 2016) - Olson, Elizabeth A.; Weber, Mareen; Rauch, Scott L.; Killgore, William D. S.
Abstract : Sleep deprivation is associated with performance decrements on some measures of executive functioning. For instance, sleep deprivation results in altered decision making on the Iowa Gambling Task. However, it is unclear which component processes of the task may be driving the effect. In this study, Iowa Gambling task performance was decomposed using the Expectancy-Valence model. Recent sleep debt and greater daytime sleepiness were associated with higher scores on the updating parameter, which reflects the extent to which recent experiences are emphasized over remote ones. Findings suggest that the effects of insufficient sleep on IGT performance are due to shortening of the time horizon over which decisions are integrated. These findings may have clinical implications in that individuals with sleep problems may not integrate more temporally distant information when making decisions.